GAMBARAN KADAR UREUM DAN KREATININ SERUM PADA PASIEN GAGAL GINJAL KRONIS (GGK) YANG MENJALANI TERAPI HEMODIALISIS DI RSUD SANJIWANI GIANYAR - ida arjani (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2016)
The kidneys are responsible for filtering waste from the body such as urea, uric acid, and creatinine. When these organs stop functioning properly, waste builds up to high levels in the blood. In patients with kidney failure are usually equipped with a blood chemistry that urea and serum creatinine as an amplifier diagnosis of the patient's illness. CKD is the progressive loss of function of kidney and patient requires a long treatment in the form of renal replacement therapy. Hemodialysis is one of the renal replacement therapy, during waste products of the body are removed. Patients with kidney failure are associated with increased levels of some biochemical parameters. In several studies, urea and creatinine serum of CKD patients pre-dialysis revealed abnormal levels and indicated hyperuremic. Therefore, this study was aimed to analyzed urea and creatinine serum in CKD patient undergoing hemodialysis in Sanjiwani Hospital. A description study, used purposive sampling methods, involving 30 patients with CKD undergoing hemodialysis. Blood samples were analyzed for urea and creatinin level. Data are presented as table. Results of this study showed that all samples (100%) had serum urea and creatinine levels high or exceed the normal limits. While of urea/creatinine levels as many as 20 patients (66,7%) had low ratio, 7 patients (23,3%) had a normal ratio, and 3 patients (10%) have a high ratio, so that it can be concluded that all patients had hyperuremic. Key words: Urea, Creatinine, Hemodialysis